Basic pharmacology for nurses - Clayton, Bruce D. , 1947-; Willihnganz, Michelle J. (Elsevier/Mosby, 2013)
"Basic Pharmacology for Nurses is a modern classic nursing pharmacology textbook known for its impeccably accurate drug content and its practical applications of the nursing process. A consistent emphasis on health promotion through monitoring and patient education is a hallmark of the book. Introductory units ground the reader in basic principles of pharmacology and medication administration. Subsequent body-system units apply the nursing process to every major disorder, and appropriate nursing implications are discussed for every drug class to promote safe medication administration."-- Publisher's website